The Importance of Christian Democracy Understanding on European Integration process from the past to the future - Pamuk, Nilhay Usta (My University, 2010)
Avrupa Birliği’nin günümüz dünyasında politik ve ekonomik arenadaki önemli aktörlerden biri olduğu bilinen bir gerçektir. Ancak bu yapının şu anki pozisyonuna bir anda gelmediği de bir diğer gerçektir. Bu tez uzun bir süreç sonucunda kurulan bu yapılanmanın oluşmasında öncülük edenler arasında belki de en önemlileri olarak Hristiyan Demokratların gösterebileceğini çünkü onların Birliğin yapı taşını oluşturacak her türlü girişimde lider pozisyonda olduklarını ileri sürmektedir. Bu çerçevede tezde Hristiyan Demokratların özelliklerini, ilklerini olduğu kadar Avbrupa entegrasyonu üzerindeki etkilerini ve AB üyesi ülkleredeki şu anki durumlarını incelemey çalışmaktadır. Ayrıca bu çalışmada Türkiye’nin Avrupa Birliği’ne giriş sürecinde keskin çıkışlarda bulunan Avrupalı Hıristiyan Demokratların davranışları ve Türk tarafının buna cevabı analiz edilmeye çalışılmıştır.

It is widely acknowledged that the European Union is an important actor in political and economic arena in the world. However, European Union did not reach its present position immediately. This was a long process and this thesis mainly claims that among the pioneers of this integration and world actorness, Christian Democrats have been the most significant actors among others; because they have been at leader position in every initiative that consisted of the building- stones of the European Union. Therefore, in this study principles and main features of Christain Democrats as well as their influence on European Integration and present status in different EU member states are examined. In addition to these questions, this study also tries to present a brief analysis of European Christian Democrats’ position about Turkey’s membership process.
Keywords: Avrupa Birliği_Türkiye; Uluslararası İlişkiler